The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1364/boe.426653
|View full text |Cite
|
Sign up to set email alerts
|

Stokes polarization imaging applied for monitoring dynamic tissue optical clearing

Abstract: We propose a continuous Stokes imaging system with a refresh rate of several seconds, instead of a traditional Mueller measurement setup, to quickly track the microstructural changes of tissues during the optical clearing process. The effectiveness of this fast Stokes imaging applied in monitoring the dynamic process is first validated by three designed experiments with a polarization state that changes continuously and rapidly, and is further confirmed by gradual changes in polarization image contrast and res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…At the same time, the polarized light path need not be designed separately, as long as the current dynamic light scattering light path-polarizing element can be added. At present, it has been applied to biomedicine ( Xiang-Yu et al, 2019 ; He et al, 2021 ; Meng et al, 2021 ; Shen et al, 2021 ; Song et al, 2021 ), marine microbial detection ( Wang et al, 2018 ; Li et al, 2020; Liu et al, 2020 ; Wang et al, 2020 ; Li et al, 2021 ), atmospheric detection ( Li et al, 2019 ; Qizhi et al, 2021 ), etc. It is believed that with the introduction of polarized light technology, the accuracy, measurable parameters, and applicable range of the dynamic light scattering method will be greatly improved.…”
Section: Online Detection Of Nanoparticlesmentioning
confidence: 99%
“…At the same time, the polarized light path need not be designed separately, as long as the current dynamic light scattering light path-polarizing element can be added. At present, it has been applied to biomedicine ( Xiang-Yu et al, 2019 ; He et al, 2021 ; Meng et al, 2021 ; Shen et al, 2021 ; Song et al, 2021 ), marine microbial detection ( Wang et al, 2018 ; Li et al, 2020; Liu et al, 2020 ; Wang et al, 2020 ; Li et al, 2021 ), atmospheric detection ( Li et al, 2019 ; Qizhi et al, 2021 ), etc. It is believed that with the introduction of polarized light technology, the accuracy, measurable parameters, and applicable range of the dynamic light scattering method will be greatly improved.…”
Section: Online Detection Of Nanoparticlesmentioning
confidence: 99%
“…Our previous work has demonstrated that Mueller matrix and polarization parameters can be used as effective tools to study the microstructural variation due to interaction between clearing agents and biological tissues [28,29]. The elements of MM contain abundant polarization information of tissue.…”
Section: Polarization Parametersmentioning
confidence: 99%
“…The polarization parameters derived from Mueller matrix by Mueller matrix polar decomposition (MMPD) can characterize features of tissues, such as the scattering coefficient, fiber structures, and anisotropy [5,6]. With the increase in the speed of polarization imaging, polarization imaging was gradually being used to study dynamic samples, not only static samples [7][8][9]. Temporal polarization images can increase the information of time dimension, and it has the potential to characterize samples with different microstructures.…”
Section: Introductionmentioning
confidence: 99%